Elevated plasma levels of WAP four-disulfide core domain 2 as a potential prognostic biomarker for various cancers - Watanabe, Makoto; Ieguchi, Katsuaki; Onishi, Nobuyuki; Shimizu, Takashi; Ohkuma, Ryotaro; Suzuki, Risako; Mura, Emiko; Iriguchi, Nana; Ishiguro, Tomoyuki; Hirasawa, Yuya; Ikeda, Go; Shimokawa, Masahiro; et al. (Frontiers in Oncology, 2025)
BackgroundAlthough WAP four-disulfide core domain 2 (WFDC2) is widely recognized as a diagnostic biomarker for ovarian cancer, its function in other cancer types remains unclear. The aim of this study was to evaluate the prognostic potential of WFDC2 across multiple cancers.MethodsPublicly available transcriptomic datasets were analyzed to compare WFDC2 mRNA expression in normal and tumor tissues across various cancer types. Kaplan-Meier survival analysis and Cox proportional hazards regression were used to assess the association between WFDC2 mRNA expression and overall survival (OS). Plasma WFDC2 levels were measured using enzyme-linked immunosorbent assay in healthy donors as well as patients with gastric, lung, colorectal, esophageal, and pancreatic cancers. Receiver operating characteristic (ROC) analysis was performed to evaluate the diagnostic performance of WFDC2. Kaplan–Meier analysis was conducted to evaluate the association between WFDC2 expression and OS. Cox proportional hazards regression analysis was performed to assess the prognostic significance of WFDC2 expression.ResultsWFDC2 mRNA expression was significantly elevated in gastric cancer, lung adenocarcinoma (LUAD), esophageal carcinoma, and pancreatic ductal adenocarcinoma (p < 0.01); however, it was significantly lower in colorectal cancer (p < 0.005). Kaplan-Meier analysis indicated that elevated WFDC2 mRNA expression in LUAD was only significantly associated with prolonged OS (p = 0.017), whereas no significant associations were observed in other cancer types. Moreover, plasma WFDC2 levels were significantly higher in all cancer patient groups than in healthy donors (p < 0.0001). ROC analysis revealed potential diagnostic performance, with an area under the curve of 0.890 (95% CI: 0.844–0.936) for distinguishing patients with cancer from healthy donors. Subgroup analysis indicated diagnostic performance across all cancer types. Elevated plasma WFDC2 levels were significantly associated with shorter OS in esophageal cancer (p = 0.0226). Multivariate Cox regression analysis confirmed that plasma WFDC2 concentration was an independent prognostic factor in gastric (HR = 1.04, 95% CI: 1.00–1.07, p = 0.019) and esophageal cancers (HR = 1.08, 95% CI: 1.02–1.13, p = 0.006).ConclusionPlasma WFDC2 levels demonstrated potential diagnostic performance across multiple cancers and were significantly associated with poor prognosis in gastric and esophageal cancers.